Legal Aspects of Child Health care - Hendrick, Judith (London : Chapman & Hall, 1997)
Legal Aspects of Child Health Care considers some of the most pressing issues in modern health law. In three parts, the book outlines the legal system and court structure, examines professional practice and finally looks at specialist areas.
Includes bibliographical references and index.
Keywords: Children -- Health and hygiene -- Law and legislation -- Great Britain; Law